Why do firms use high discount rates? - Jagannathan, Ravi; Matsa, David A.; Meier, Iwan; Tarhan, Vefa (Journal of Financial Economics, 2016)
We present evidence consistent with operational constraints leading firms to use high discount rates that average twice the firms’ cost of financial capital. Based on a survey of Chief Financial Officers matched to archival data, we find that firms with abundant access to capital but limited qualified management or manpower appear to forgo profitable projects in preparation for more profitable future investment opportunities. Consistent with this explanation, firms that use high discount rates have strong balance sheets, low leverage, and large cash holdings. In addition, firms appear to increase discount rates to account for idiosyncratic risk.